2016
DOI: 10.1590/1678-4324-2016160321
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals in Garra gotyla , Cyprinus carpio and Cyprinion watsoni from the River Panjkora, District, Lower Dir, Khyber Pakhtunkhwa, Pakistan

Abstract: This study was conducted in the River Panjkora, Pakistan, in order to assess the level of heavy metals accumulated in the liver, kidneys, gills and muscle tissues of three highly consumed fish species by the local community, Garra gotyla, Cyprinus carpio and Cyprinion watsoni. The heavy metals including manganese (Mn), iron (Fe), chromium (Cr), zinc (Zn), lead (Pb), cadmium (Cd) and nickel (Ni) were determined in the collected fish specimens through an atomic absorption spectrophotometer. Level of heavy metals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Pollutants accumulating in food chains through biomagnification have been particularly well‐documented in marine mammals (Kuhnlein et al 1995; Binnington et al 2016), seafood (Donatuto et al 2011), riverine fish (Ullah et al 2016), birds (Bidleman et al 2010), large mammals (Doyle et al 2012), and caribou (Ostertag et al 2009), and IPs in many areas depend heavily on these foods. Several studies have shown that global warming may increase pollution levels in fish and marine mammals by increasing rates of ecological mobilization and biomagnification (Jenssen 2006; Dudley et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Pollutants accumulating in food chains through biomagnification have been particularly well‐documented in marine mammals (Kuhnlein et al 1995; Binnington et al 2016), seafood (Donatuto et al 2011), riverine fish (Ullah et al 2016), birds (Bidleman et al 2010), large mammals (Doyle et al 2012), and caribou (Ostertag et al 2009), and IPs in many areas depend heavily on these foods. Several studies have shown that global warming may increase pollution levels in fish and marine mammals by increasing rates of ecological mobilization and biomagnification (Jenssen 2006; Dudley et al 2015).…”
Section: Resultsmentioning
confidence: 99%